2014
DOI: 10.1097/mot.0000000000000112
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of allograft vasculopathy in cardiac transplantation

Abstract: CAV is an important complication-limiting survival after heart transplant, and a clear understanding of the underlying pathophysiological processes is important. The diagnosis of CAV can be difficult, but it is possible with the appropriate imaging modalities. Effective treatment of CAV remains an important clinical challenge, and current immunosuppressive therapy has limited efficacy. However, newer immunosuppressive agents have demonstrated promising results in clinical trials, and this will hopefully allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…The immunobiology of vasculopathy has been studied in great detail in cardiac transplantation . The term is sometimes used interchangeably with chronic rejection, but evidence suggests vasculopathy is more complex than an incompletely controlled rejection response, although suboptimal immunosuppression has been shown to induce vasculopathy in animal models .…”
Section: Tissue Components Of Composite Allograftsmentioning
confidence: 99%
“…The immunobiology of vasculopathy has been studied in great detail in cardiac transplantation . The term is sometimes used interchangeably with chronic rejection, but evidence suggests vasculopathy is more complex than an incompletely controlled rejection response, although suboptimal immunosuppression has been shown to induce vasculopathy in animal models .…”
Section: Tissue Components Of Composite Allograftsmentioning
confidence: 99%
“…These data support that adventitial macrophages may enhance mural cell miR-21 expression via a paracrine mechanism. Given the pivotal role of proliferation and migration of medial SMCs in the development of transplant vasculopathy [35, 7], and the well documented detrimental effects of miR-21 in pathological vascular remodeling [19, 27, 29, 30, 37, 38], we suggest that the observed beneficial effects of macrophage depletion in aortic allografts are, at least in part, due to reduced miR-21 expression in vascular mural cells.…”
Section: Discussionmentioning
confidence: 87%
“…For example, population studies have suggested that around 90% of patients receiving heart transplantation will develop transplant vasculopathy within 10 years [6]. Transplant vasculopathy is also known as transplant arteriosclerosis, which is characterized by progressing neointimal hyperplasia, luminal stenosis, and finally ischemic graft failure [35]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in abnormal cell proliferation and protein synthesis via the activation of p70 ribosomal S6 kinase and eukaryotic initiation factor 4E‐binding protein . Cytokines released by activated T‐lymphocytes also activate donor endothelial cells and promote expression of adhesion molecules (intercellular adhesion molecule‐1, vascular adhesion molecule‐1, and P‐selectin), which mediate further recruitment and accumulation of T‐lymphocytes and macrophages in the vessel intima, leading to a sustained inflammatory response . Macrophages secrete cytokines and growth factors that further stimulate the proliferation and migration of coronary smooth muscle cells to promote abnormal intimal thickening and extracellular matrix deposition .…”
Section: Pathogenesismentioning
confidence: 99%